Evaluation of physical and chemical isolation methods to extract and purify Campylobacter jejuni extracellular polymeric substances - Pavlinjek, Natalija; Klančnik, Anja; Sabotič, Jerica (Frontiers in Microbiology, 2024)
The pathogenic bacterium Campylobacter jejuni is a major food safety concern as it can form biofilms that increase its survival and infective potential. Biofilms consist of microbial cells and extracellular matrix (ECM), which is made of water and extracellular polymeric substances (EPS), which are critical for structural integrity and pathogenicity. The aim of this study was to optimize a protocol for the isolation of C. jejuni ECM. We employed eight physical and chemical isolation methods to extract and purify ECM, followed by different qualitative and quantitative analyses using gel electrophoresis and spectroscopy. This comprehensive approach enabled the evaluation of ECM composition in terms of polysaccharides, proteins, and extracellular DNA. The isolation methods resulted in different yields and purities of the extracted ECM components. Centrifugation in combination with chemical treatments proved to be most effective, isolating higher concentrations of polysaccharides and proteins. Additionally, extraction with ether solution facilitated the recovery of high-molecular-weight extracellular DNA. Overall, we provide a refined methodology for ECM extraction from C. jejuni. As polysaccharides and proteins participate in biofilm stability and microbial communication, and extracellular DNA participates in genetic exchange and virulence, our study contributes towards a better understanding of the persistence of this pathogen in the food industry.